Comparative Analysis of Media. The Transformation of Relations between Script and Image − from Analogue Media to Interactive Environment - Smaga, Agnieszka (Załącznik Kulturoznawczy, 2023)
A digital communiqué operates with GUI not to depict, describe or structure the meanings but, above all, to transfer them. At the moment of clicking, that is, when a specific question is being asked by the user (customer), specific semiotically varied content is downloaded and displayed on the screen in accordance with the pre-designed, graphic template. Thus, graphical interface treats writing and image on the one hand as heterogeneous units – stored in databases, in a way that makes them quick and easy to find; on the other hand – heteronomous, that is, affecting each other at the level of presentation and manipulation of the message. Graphical edition skillfully combines the expectations of recipients concerning the access to the message: on the one hand – precise (along the lines of the language), on the other – economic, reducing (iconic), and it merges in this way two structures of reception, considered in our culture to be different.Pragmatic functionality of digital message is understood as accurate and synthetic mediation, which results in further analogous features from the level of semiotics and semantics, where the highlighted three planes of the communiqué circulate in the feedback loop.